2022
DOI: 10.3389/fonc.2022.836352
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Mucoepidermoid Carcinoma: A Review of 58 Cases

Abstract: BackgroundEsophageal mucoepidermoid carcinoma (EMEC) is a rare disease. The biological behavior and treatment of this malignancy are not well established.MethodsData from 58 patients with EMEC who underwent esophagectomy were retrospectively analyzed and compared with 5028 patients with esophageal squamous cell carcinoma (ESCC). Kaplan–Meier and multivariate Cox regression analyses were conducted to investigate the association between clinicopathological factors and survival.ResultsThe study cohort included 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, some scholars argue that MECE might originate from squamous epithelium, considering its extension into and infiltration of squamous tissue, predilection for certain sites, close association with dysplastic epithelial areas, and prognosis similar to squamous cell carcinoma [ 10 ]. As reported by Ozawa [ 5 ] and Chen [ 3 ], who noted a 0% accuracy rate for preoperative endoscopic diagnosis of MECE, Wang [ 11 ] observed that in a study of 47 patients, only one was diagnosed with MECE preoperatively via endoscopy, while the others were predominantly misdiagnosed as squamous cell carcinoma. In our series, the preoperative endoscopic diagnosis accuracy was only 6.3% (3/48), with MECE more frequently misdiagnosed as squamous carcinoma than adenocarcinoma (28 cases vs. 8 cases).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, some scholars argue that MECE might originate from squamous epithelium, considering its extension into and infiltration of squamous tissue, predilection for certain sites, close association with dysplastic epithelial areas, and prognosis similar to squamous cell carcinoma [ 10 ]. As reported by Ozawa [ 5 ] and Chen [ 3 ], who noted a 0% accuracy rate for preoperative endoscopic diagnosis of MECE, Wang [ 11 ] observed that in a study of 47 patients, only one was diagnosed with MECE preoperatively via endoscopy, while the others were predominantly misdiagnosed as squamous cell carcinoma. In our series, the preoperative endoscopic diagnosis accuracy was only 6.3% (3/48), with MECE more frequently misdiagnosed as squamous carcinoma than adenocarcinoma (28 cases vs. 8 cases).…”
Section: Discussionmentioning
confidence: 90%
“…A literature review by Kumagai [ 14 ] of multiple studies from different hospitals and countries revealed a lymph node metastasis rate of 48.9% (45/92) in 92 MECE patients. Chen [ 3 ] and Wang [ 11 ] reported lymph node metastasis rates of 22.3% and 25.0%, respectively, significantly lower than the 49.4% in ESCC patients ( P < 0.001). Our study showed a lymph node metastasis rate of 35.4% (17/48) in MECE patients, which did not significantly differ from that in ESCC (45.5%, P = 0.165) but was higher than in EAC (21.4%, P = 0.034).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following types of tumors should be considered: gastrointestinal stromal tumor (GIST), solitary fibrous tumor (SFT), schwannoma, perivascular epithelioid cell tumor (PEComa), and a sclerosing variant of well-differentiated liposarcoma. Extra-GISTs are rare, but several cases have been reported [ 32 36 ]. Tumors in the greater omentum are frequently diagnosed as GIST [ 34 ].…”
Section: Discussionmentioning
confidence: 99%